Some Practical Aspects of Pluralism - Thomas Mayer (University of California, Department of Economics, 1999)
This contribution to a Festschrift for Warren Samuels argues that in giving policy advice economists should seek diversification and consider the probability of error, and also the loss function and risk aversion. And since advocacy of a theory is in a relevant way like a policy decision, the same applies to theories. If this means employing contradictory theories, then that is consistent with rational behavior. In choosing a methodology, too, a sharp dichotomy of right and wrong is not useful, as the example of new classical reductionism illustrates. Similarly, there is a role for probabilistic pluralism in making value judgments.
Keywords: 330